Colistin Resistance and ESBL Production in Salmonella and Escherichia coli from Pigs and Pork in the Thailand, Cambodia, Lao PDR, and Myanmar Border Area - Khin Khin Lay; Saharuetai Jeamsripong; Kyaw Phyoe Sunn; Sunpetch Angkititrakul; Ransiya Prathan; Songsak Srisanga; Rungtip Chuanchuen (MDPI AG, 2021)
The study aimed to examine the prevalence and genetic characteristics of ESBL-production and colistin resistance in Salmonella and Escherichia coli from pigs and pork in the border area among Thailand, Cambodia, Lao PDR, and Myanmar. Salmonella (n = 463) and E. coli (n = 767) isolates were collected from pig rectal swab from slaughterhouses (n = 441) and pork from retail markets (n = 368) during October 2017 and March 2018. All were determined for susceptibility to colistin and cephalosporins, ESBL production and mcr and ESBL genes. Salmonella was predominantly found in Cambodia (65.8%). Serovars Rissen (35.6%) and Anatum (15.3%) were the most common. The E. coli prevalence in pork was above 91% in all countries. Colistin-resistance rate in E. coli (10.4%) was significantly higher than Salmonella (2.6%). ESBL-producing Salmonella (1.9%) and E. coli (6.3%) were detected. The blaCTX-M-55 and blaCTX-M-14 were identified. The mcr-1 gene was detected in Salmonella (n = 12) and E. coli (n = 68). The mcr-1/blaCTX-M-55 and mcr-3/blaCTX-M-55 co-concurrence was observed in one Salmonella and three E. coli isolates, respectively. In conclusion, pigs and pork serve as carriers of colistin and new generation cephalosporins resistance. Testing for resistance to last line antibiotics should be included in national AMR surveillance program using One Health approach.